The Moral Minorities: A Self-Report Study of Low-Consensus Deviance - Winslow, Robert W. (International journal of offender therapy and comparative criminology, 1993)
Much sociological literature, both past and present, supports the status quo position that minorities and the poor are responsible for much, if not most, crime and delinquency. Data are presented from a survey of 1,035 students at a large Western university, which suggest that members of minority and low-income groups are actually less deviant than their more affluent, white classmates, at least in regard to acts of "low-consensus deviance." These are acts that pertain to traditional morality, including sexual activity, alcohol consumption, and drug usage. It is suggested that minorities and the poor traditionally are found to be more deviant than the less poor white majority because of the "criminalizing" or crime-inducing effect of law enforcement to which the underclass is disproportionately exposed. Further, it is proposed that formal exposure to law enforcement is a better predictor of serious deviance than either race or income